PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DI KELAS II SEKOLAH DASAR - Shintia; Susilawati, Wiwik Okta; Anggrayni, M. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The main problem in this study is how to apply the jigsaw cooperative learning model to improve learning outcomes in grade II students of SDN 14 Pulau Punjung? This study aims to improve the learning outcomes of grade II students of SDN 14 Pulau Punjung. This type of research is classroom action research consisting of two cycles where each cycle is carried out in two meetings. The research procedure includes planning, implementation of actions, observation and reflection. The subjects in this study were 12 students of class II SDN 14 Pulau Punjung. The results of the study showed that in the first cycle that was completed individually from 12 people, only 5 students or 41.67% met the KKTP and 7 students or 58.33% did not meet the learning objective achievement criteria (KKTP) by obtaining an average score of 56.76%. While in the second cycle where from 12 students there were 10 students or 83.33% who had met the learning objective achievement criteria and had a very high score with an average of 72.66%. Based on the results of the study above, it can be concluded that the learning outcomes of class II students of SDN 14 Pulau Punjung through the application of the jigsaw type cooperative learning model have increased.